Urban flooding SAM : system based analysis and management of urban flood risks : dissemination conference : 19th May 2009 - Venables, Jean (Thomas Telford, 2009)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of the dissemination conference held on 19 May 2009.